2015
DOI: 10.1016/j.jaci.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

TNF-related apoptosis-inducing ligand (TRAIL) regulates midline-1, thymic stromal lymphopoietin, inflammation, and remodeling in experimental eosinophilic esophagitis

Abstract: Background Eosinophilic Oesophagitis (EoE) is an inflammatory disorder of the oesophagus defined by eosinophil infiltration and tissue remodelling with resulting symptoms of oesophageal dysfunction. Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) promotes inflammation by upregulation of the E3 ubiquitin-ligase midline-1 (MID1), which binds to and deactivates the catalytic subunit of protein phosphatase 2 A (PP2Ac) resulting in increased NF-κB activation. Objective To elucidate the role of TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…TSLP is overexpressed in esophageal biopsies from individuals with EoE as compared to unaffected individuals, while WDR36 expression is unaltered, implicating the 5q22 locus (and TSLP in particular) in the pathogenesis of EoE [48]. Animal models also support a role for TSLP in EoE pathogenesis [150•]. In a murine epicutaneous sensitization model of EoE, esophageal inflammation is dependent in part of TSLP and basophils, but independent of IgE.…”
Section: Cytokines Chemokines and Other Moleculesmentioning
confidence: 99%
“…TSLP is overexpressed in esophageal biopsies from individuals with EoE as compared to unaffected individuals, while WDR36 expression is unaltered, implicating the 5q22 locus (and TSLP in particular) in the pathogenesis of EoE [48]. Animal models also support a role for TSLP in EoE pathogenesis [150•]. In a murine epicutaneous sensitization model of EoE, esophageal inflammation is dependent in part of TSLP and basophils, but independent of IgE.…”
Section: Cytokines Chemokines and Other Moleculesmentioning
confidence: 99%
“…inflammation of the esophagus (17). In allergic disease settings, we observed that Tnfsf10 Ϫ/Ϫ mice were protected from AHR associated with reduced mast cell numbers and eosinophilic inflammation (14,60).…”
Section: Discussionmentioning
confidence: 83%
“…It is not yet known if TRAIL modulates apoptosis during RV infection in vivo, or whether it has any effect on virus replication and/or inflammation. It was shown previously that TRAIL promoted inflammatory responses in the context of allergic inflammation of the lung and esophagus, neonatal Chlamydia infection, and cigarette smoke-induced COPD (14,15,17,31,53,60).…”
mentioning
confidence: 93%
“…42,53 TNFa/TRAIL drive MID1 expression in asthma and esophageal eosinophilia. 54,55 It was determined whether TNFa increases Trail and Mid1 independent of MT-COMP expression in RCS cells, as this TNFa increase in MID1 was previously shown in the epithelial cells lining the airway. 55 TNFa treatment (200 ng/mL) in RCS cells for 72 hours increased both Trail and Mid1 mRNAs by 33-and 16-fold, respectively ( Figure 3K).…”
Section: Mid1 Is Increased By Er Stress and Tnfa/trail Inflammationmentioning
confidence: 99%
“…54,55 It was determined whether TNFa increases Trail and Mid1 independent of MT-COMP expression in RCS cells, as this TNFa increase in MID1 was previously shown in the epithelial cells lining the airway. 55 TNFa treatment (200 ng/mL) in RCS cells for 72 hours increased both Trail and Mid1 mRNAs by 33-and 16-fold, respectively ( Figure 3K). Consistent with these findings, both TNFa and TRAIL immunostaining were also increased in MT-COMP mice compared to controls (Figure 3, AeJ).…”
Section: Mid1 Is Increased By Er Stress and Tnfa/trail Inflammationmentioning
confidence: 99%